To determine the GCD of the polynomials x3+x+1x^3 + x + 1x3+x+1 and x2+x+1x^2 + x + 1x2+x+1 over the finite field GF(2)GF(2)GF(2), we will use polynomial division and the Euclidean algorithm.
Step 1: Understand the field GF(2)GF(2)GF(2)
In GF(2)GF(2)GF(2), the arithmetic is modulo 2, meaning:
- 1+1=01 + 1 = 01+1=0
- 1×1=11 \times 1 = 11×1=1
- 0+0=00 + 0 = 00+0=0
Step 2: Perform polynomial division
We need to divide x3+x+1x^3 + x + 1x3+x+1 by x2+x+1x^2 + x + 1x2+x+1 over GF(2)GF(2)GF(2).
Division process:
- Divide the leading term: x3x^3x3 by x2x^2x2, which gives xxx.
- Multiply: x⋅(x2+x+1)=x3+x2+xx \cdot (x^2 + x + 1) = x^3 + x^2 + xx⋅(x2+x+1)=x3+x2+x.
- Subtract (remember, subtraction is the same as addition in GF(2)GF(2)GF(2)): (x3+x+1)−(x3+x2+x)=x2+1.(x^3 + x + 1) - (x^3 + x^2 + x) = x^2 + 1.(x3+x+1)−(x3+x2+x)=x2+1.
- Divide the leading term: x2x^2x2 by x2x^2x2, which gives 111.
- Multiply: 1⋅(x2+x+1)=x2+x+11 \cdot (x^2 + x + 1) = x^2 + x + 11⋅(x2+x+1)=x2+x+1.
- Subtract: (x2+1)−(x2+x+1)=x.(x^2 + 1) - (x^2 + x + 1) = x.(x2+1)−(x2+x+1)=x.
Thus, after division, we are left with the remainder xxx, meaning the GCD is the last non-zero remainder.
Step 3: Conclusion
The GCD of x3+x+1x^3 + x + 1x3+x+1 and x2+x+1x^2 + x + 1x2+x+1 over GF(2)GF(2)GF(2) is 1\boxed{1}1, because we reached a remainder of 1, indicating that the two polynomials are coprime (i.e., they have no common factors other than 1).
Correct Answer:
(a) 1